Analysis of Net Profit on Assets and Net Margin as a Measure of Company Value - Khalik, Nur Zaman (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2021)
Many companies are trying to increase the value of the company, this is done, because the management is aware of the limitations, and the importance of long-term investment for the progress of the company. This study tries to analyze financial fundamentals, namely in terms of net income from assets. The research method is based on quantitative, namely analyzing financial statement data as a source of analysis. The object of research is PT Antam Tbk, with the amount of data used for 11 years (2010-2020). The data was taken based on the determination of the criteria, namely purposively. The results of the study stated that the increase in the value of PT Antam's company was due to good profits, especially the aspect of net profit margin. In other words, NPM is the main source in PT Antam's earnings management, thereby leading to a better market response. What is interesting is the contribution value of ROA and NPM, showing a large portion, namely 71.5%. This confirms, if profit is the main factor in increasing the value of the company.